Teaching Thinking Skills in Teacher Education - Nur Qistina, Christina Andin @; Ambotang, Abdul Said; Mosin, Musirin (EDUCARE, 2015)
ABSTRACT: The thinking skills policy in Malaysia is motivated by the aspiration of the 2020 Vision that was published in 1991. The vision states explicitly that Malaysia will become a fully developed nation by the year 2020. So, teaching the thinking skills has also been given a high priority in educational policy. However, many teachers are ill-equipped with the ability to teach thinking skills. Therefore, as the producer of current and future teacher, teacher education programme should emphasize thinking skills teaching. This study aimed at identifying the extent to which teacher educators provide an exemplary practice of thinking skills teaching to student teachers. Specifically, this study investigates whether teacher educators provide the opportunity to student teachers to engage in teaching and learning that emphasized the integration of thinking skills. This study was conducted at one teacher education programme in Malaysia. All final year student teacher (60) were selected as the samples. A set of questionnaire used as an instrument. Data were analyzed using Statistical Package for the Social Science and the findings were reported in the form of frequency and percentage. The findings indicate the lack integration of various forms of thinking skills in teaching and learning activities. The traditional approach of a one-way communication technique was more dominant compare to the teaching technique that promotes thinking skills. Hence, this study has several practical implications for teacher education programme for producing future teachers with the ability to implement thinking skills policy in schools. KEY WORDS: Thinking skills, educational policy, teacher education, teacher educator, student-teacher, teaching and learning activities, and ability to implement thinking skills policy.Â Â Â Â About the Authors: Christina Andin @ Nur Qistina, Abdul Said Ambotang and Musirin Mosin are the Lecturers at the Faculty of Psychology and Education UMS (Malaysia University of Sabah), 88400 Kota Kinabalu, Sabah, Malaysia. For academic interests, the authors can be contacted via their e-mails at: christina@ums.edu.my, said@ums.edu.my, and m_musirin@yahoo.comHow to cite this article? Nur Qistina, Christina Andin @, Abdul Said Ambotang & Musirin Mosin. (2015). âTeaching Thinking Skills in Teacher Educationâ in EDUCARE: International Journal for Educational Studies, Vol.8(1) August, pp.31-44. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877.Â Chronicle of the article: Accepted (May 14, 2015); Revised (June 29, 2015); and Published (August 25, 2015).